Mycotoxins and Food Safety - Sabuncuoğlu, Suna (IntechOpen, 2020)
Foodborne illnesses are a global public health concern with implications worldwide. Mycotoxins are naturally occurring toxins produced by microfungi that are capable of causing disease and death in. living organisms. They are recognized as a major economic problem due to their impact on human health, animal productivity, and.domestic and.international.trade. This book provides updated information about foodborne mycotoxins, their toxicities, new determination methods, prevention strategies, and regulations around the world.